THE EFFECTIVENESS OF VILLAGE GOVERNANCE IN THE IMPLEMENTATION OF VILLAGE FUNDS IN WRINGINJAJAR VILLAGE - Asharri, Fahmi; Astuti, Retno Sunu (Journal of Public Policy and Management Review, 2019)
The Indonesian government for the 2014-2019 period carried a program called Nawacita. The third point in Nawacita provides an understanding that the focus of development is spread even by strengthening suburban and village areas. Through Minister of Finance Regulation No. 93 of 2015, states that Village Funds are channeled from the State General Cash Account to the Regional General Cash Account every new fiscal year. The government's attention to Demak Regency related to village management is shown through Regent Regulation Number 8 of 2017. In this study using Qualitative Research Methodology with a purposive sampling approach. The results of this study indicate that in the management of village funds not in accordance with the principles of good governance, in the principle of participation, the community is still lacking in contributing ideas or ideas to the village, on the principle of transparency, the village government seems closed in village fund management and on the principle of accountability the responsibility of the village government for reports on the results of activities does not reach the community and its BPD working partners. The influencing factors include filling in non-professional positions, limited collaboration between village officials in carrying out tasks and relations between village institutions. The recommendations given are providing training to the village secretary, understanding the duties and functions of each village apparatus, and providing access to information to the BPD and the community.